2018
DOI: 10.1021/acs.jpcb.8b06148
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvents for Induced Circularly Polarized Luminescence

Abstract: Materials that emit circularly polarized light have application in several important industries. Deep eutectic solvents (DES) with chiral components are attractive as solvents of luminescent lanthanides for the development of chiral light-emitting materials. Deep eutectic solvents are prepared with combinations of tetrabutylammonium (or tetrabutylphosphonium) chloride as hydrogen bond acceptor (HBA) and amino acids, l-and d-glutamic acid, l-proline, and l-arginine as hydrogen bond donor (HBD). A racemic mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 59 publications
3
36
0
Order By: Relevance
“…A large set of molecules was tested as counterpart of L-Proline (L-Pro) to prepare DESs liquids at room temperature. In this screening, molecules that formed DESs with other counterparts reported in literature were tested, as well as other hydrogen-bond capable molecules; L-Pro was tested as HBA as well as HBD since it is known its dual role [46,47]. Urea, choline chloride, acetamide, (1S)-(+)-10-camphorsulfonic acid, tetramethylammonium chloride, D-(+)-glucose, ZnCl2, 1,6-hexanediol, S-(+)-mandelic acid, picolinic acid, L-(+)-tartaric acid, citric acid and phenol were tested in the molar ratio range from 0.5:1 to 8:1 with L-Pro.…”
Section: Preparation Of Novel L-proline-based Deep Eutectic Solventsmentioning
confidence: 99%
“…A large set of molecules was tested as counterpart of L-Proline (L-Pro) to prepare DESs liquids at room temperature. In this screening, molecules that formed DESs with other counterparts reported in literature were tested, as well as other hydrogen-bond capable molecules; L-Pro was tested as HBA as well as HBD since it is known its dual role [46,47]. Urea, choline chloride, acetamide, (1S)-(+)-10-camphorsulfonic acid, tetramethylammonium chloride, D-(+)-glucose, ZnCl2, 1,6-hexanediol, S-(+)-mandelic acid, picolinic acid, L-(+)-tartaric acid, citric acid and phenol were tested in the molar ratio range from 0.5:1 to 8:1 with L-Pro.…”
Section: Preparation Of Novel L-proline-based Deep Eutectic Solventsmentioning
confidence: 99%
“…Among these, there are several examples of applications of DES used as electrolytes in electroluminescent materials, batteries, and electrochromic devices [12–19] . Incorporation of a chiral HBA and/or HBD can lead to their use as solvents for circularly polarized light emitting materials [20,21] …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that CPL can be induced through a non‐covalent chiral discrimination interaction between chiral DES, as solvent, and a racemic mixture of luminescent lanthanide complexes, Λ‐ and Δ‐Ln(dpa) 3 3− (where dpa=2,6‐pyridinedicarboxylate dianion, and Ln=Eu 3+ or Tb 3+ ) [20,21] . This coordination complex, Ln(dpa) 3 3− , exists in solution as a racemic mixture of interconverting left‐handed (Λ) or right‐handed (Δ) enantiomers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations